Annexin A2 Expression in Aerogenous Metastasis of Pulmonary Invasive Mucinous Adenocarcinoma: A Case Report including Immunohistochemical Analysis - Kazumori Arai; Masahide Hirose (Case Reports in Oncological Medicine)
Aerogenous metastasis (AM) is a form of lung cancer that spreads in a unique fashion, but its mechanisms are still unclear. Annexin A2 (ANX A2), a membrane-binding protein, promotes cancer invasion and is involved in cell adhesion and polarity. The relationship between ANX A2 and cancers with poor stromal invasion capacity has not been studied. We immunohistochemically analyzed ANX A2 expression in AM observed in a patient with pulmonary invasive mucinous adenocarcinoma. In the primary site, ANX A2 immunopositivity on the cell-cell borders weakened as tumor cells projected and separated into alveolar spaces. In AM, tumor cell aggregates with ANX A2 immunopositivity near the surface and within the cytoplasm attached to alveolar epithelial cells, then engulfed them and formed a protrusion. As tumor cell aggregates adhered to the alveolar wall and formed a single layer, cytoplasmic ANX A2-positive products accumulated in the lateral sides of the tumor cells and exhibited distinct membranous positivity. These results indicated that ANX A2 near the tumor cell surface was related to alveolar wall attachment. Furthermore, the translocation of cytoplasmic ANX A2 to cell-cell borders changed cell morphology, adhesion, and polarity restoration.